Representasi hedonisme budaya lebaran dalam iklan televisi: Pendekatan Teori Representasi Pierre Bourdieu - Sari, Novita (Maliki Interdisciplinary Journal, 2024)
The culture of Lebaran, which celebrates the end of Ramadan, has become an important celebration for Indonesians. In recent years, television advertisements have become a popular medium to portray the spirit and traditions of Lebaran. This article aims to analyze the representation of Lebaran cultural hedonism in television advertisements. Hedonism, which refers to the tendency to seek pleasure and sensory enjoyment, has emerged as a dominant element in Lebaran advertisements. This article analyzes the representation of Lebaran cultural hedonism in television advertisements using Pierre Bourdieu's representation theory approach. In the context of Lebaran celebrations full of joy, delicious food and entertainment, television advertisements often play an important role in promoting hedonistic consumption. Bourdieu's representation theory approach provides a useful analytical framework for understanding how Lebaran television advertisements represent hedonism and how these representations are related to cultural capital and social structures(Kussudyarsana, 2009).